Islamic Educational Philosophy in The Testament of New Experience Reflection by TGKH. Muhammad Zainuddin Abdul Madjid - Tabibuddin, M.; Thohri, Muhammad; Wathoni, Lalu Muhammad Nurul (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research aims to explore and analyze the concepts of Islamic educational philosophy contained in the work "Testament of New Experience Reflection" by TGKH. Muhammad Zainuddin Abdul Madjid. In this study, the author conducts a profound analysis of the content of the work, identifying the values, principles, and concepts of Islamic education that can be found in the text. The research also explores the historical and cultural context in which the work was written and the relevance of the concepts found in the work to contemporary Islamic education. This research employs a philosophical approach and critical analysis to understand and evaluate the thinking of TGKH. Muhammad Zainuddin Abdul Madjid in the context of Islamic education. The results of this research can provide profound insights into the philosophy of Islamic education within the work and the contributions of the thinker to Islamic educational thought. This research is expected to contribute to a deeper understanding of Islamic education, moral values, ethics, educational goals, and methods within the context of Islam, as well as the relevance of the ideas of TGKH. Muhammad Zainuddin Abdul Madjid to contemporary Islamic education. Furthermore, this research serves as a foundation for further studies on Islamic educational thought in Indonesia.